Pengaruh Harga, Pelayanan Dan Promosi Online Terhadap Keputusan Pembelian Pada Rumah Makan Gubuk Tiwul - Monitaria, Abi Melin; Baskoro, Ery (Universitas Muhammadiyah Metro, 2021)
The rapid number of food needs has made entrepreneurs in the culinary field in Indonesia compete to set up businesses because with this, entrepreneurs in the culinary field can become one of the supports for the existing economic structure in Indonesia. This has become one of the motivations for entrepreneurs in various regions without exception, one of them in the city of Metro Lampung to carry out business activities in the culinary field. One of the places to eat in the city of Metro is the Tiwul Hut Restaurant. As for the formulation of the problem in this study, namely